Vertical posture and perineal tears in humanized childbirths - Yazmín Estefanía Cavallari-Drey; Manuel Ortiz-Llorens (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to determine the association between vertical childbirth posture and grade II or higher perineal tears in women attended under a humanized model. Methods: 715 clinical records of humanized deliveries attended between 2016 and 2022 in Viña del Mar, Chile, were studied using bivariate analysis and binary logistic regression. Results: 64.1% of the women presented perineal lesions, mainly low grade (51.2%). Second degree tears or more represented 12.2% (mostly grade II), with very few grade III tears (0.7%) and zero grade IV tears. Vertical postures, compared to horizontal ones, were significantly associated with the presence of grade II tears or more (p=0.02), even after adjusting for maternal and neonatal variables (OR=2.31, CI95%=1.11-4.81). Of the latter, parity and size of the newborn were the factors most associated with this type of injury. Conclusion: humanized childbirths in general present less frequency and severity of perineal injuries than what is reported in traditional care; however, upright postures, compared to horizontal ones, were significantly associated with the presence of grade II or higher tears.